TREN HADIS ARBAIN SUNNI DAN SYIAH ZAYDI: STUDI KOMPARATIF TERHADAP ARBAIN NAWAWIYAH, SILSILAT AL-IBRIZ, DAN ARBAUN ALAWIYAH - Muhammad Taufiqqulhidayah Nur Waarits; Via Nur Karima (Yayasan Haiah Nusratul Islam, 2026)
This study explores the tradition of collecting forty hadiths (Arba'in) within Sunni and Shia Zaydi traditions, conducting a comparative analysis of three seminal texts: Al-Arba'in al-Nawawiyah, Silsilat al-Ibriz, and Al-Arba'un al-Alawiyah. Utilizing a qualitative library research methodology with a comparative approach, this research examines the divergences in content, transmission methods (sanad), and socio-political roles of these collections. Data were gathered through text documentation and analyzed using content analysis alongside sanad criticism. The findings reveal that while sharing the structural format of Arba'in, these texts exhibit distinct theological priorities. Al-Arba'in al-Nawawiyah represents the Sunni tradition by emphasizing universally accepted hadiths on creed, worship, and ethics, validated through major companions. Conversely, Al-Arba'un al-Alawiyah reflects Zaydi Shia ideology, prioritizing the exclusive lineage of the Ahlul Bait, with a focus on Imamah, divine justice, and Sunni political critique. Meanwhile, Silsilat al-Ibriz offers an inclusive, spiritual approach emphasizing universal morals and explicitly avoiding sectarian narratives. The study concludes that differences in these collections stem primarily from disputes over religious authority and sanad validation rather than mere textual validity. Ultimately, despite their divergent theological and political orientations, all three collections function as dynamic tools for religious education and identity formation. Recognizing these shared educational functions, alongside the inclusive nature of Sufi-leaning texts like Silsilat al-Ibriz, offers a promising avenue for mediating sectarian tensions and fostering dialogue based on a shared Islamic heritage.